Nomenclatural priority of the diatom name Fryxelliella sepulvedana over Fryxelliella paciﬁca (Triceratiaceae, Bacillariophyta) - Aké-Castillo, José Antolín; Del Castillo, María Esther Meave; Zamudio-Resendiz, María Eugenia (Phytotaxa, 2014)
In 2008 two new species belonging to the genus Fryxelliella were described: F. sepulvedana and F. pacifica. They were based on material collected in the Pacific Ocean and were both different from Fryxelliella floridana, the type species of the genus. Examination of holotype and additional material for F. sepulvedana and F. pacifica was carried out. Comparisons confirmed that F. sepulvedana and F. pacifica are both the same species. Only one valid name can be assigned to any taxon and reasons are given to demonstrate that the valid name should be Fryxelliella sepulvedana.